Analysis of Online Purchasing Decisions through Social Media - Destine Fajar Wiedayanti (Admisi dan Bisnis, 2023)
Researchers are interested in taking the title of Online Purchase Decision Analysis Through Social Media. The analytical technique used in this study is a qualitative method, namely the translation of descriptive data through two stages of analysis corporate image variable, information quality variable, risk perception variable, web design attractiveness variable and vendor reputation variable. The trust variable is the most dominant factor influencing online purchasing decisions through social media. This is supported by 5 (five) researchers who place the trust variable as having a higher influence than other variables